Combining ability in maize for resistance to the Cercospora zeae-maydis - Engelsing, Marcio (2011)
The resistance due to genetic component is the most efficient method to control maize leaf diseases. The general combining ability (GCA), the specific combining ability (SCA), the reciprocal, the maternal and the not-maternal were evaluated for resistance to the Cercospora zeae-maydis at twenty hybrids. The hybrids were originated from crosses of five parents (A, B, C, D and E). The experiment was conducted in three environments. The resistance to Cercospora zeae-maydis was evaluated using grain yield (RG) in the harvest and the severity of Gray leaf spot (GLS) at physiological maturation, using the scale proposed by Agroceres (1996). The dialelic analysis demonstrated a significant interaction (P < 0,05) between hybrids versus places for GLS and RG. For the variable GLS, the GCA demonstrated that the best genitors had been D and E, different of that observed in grain yield (A and B). When considering SCA, the best hybrids combinations at the average places were AxD, BxE, AxE and BxC, and should be recommended the maintenance of these hybrids in the company breeding program.